PENDIRIAN PERPUSTAKAAN MI AS-SIBYAN SEBAGAI UPAYA PENINGKATAN MINAT BACA DAN AKSES PENGETAHUAN PESERTA DIDIK DI DESA NANJUNGJAYA - Putra Nur Ali Asfi Bumi; Saida Alya; Sekar Jovinta; Tazqia Putri Awwalia; Kaka Setiawan; Jajang Supriatna (Makkareso: Riset Pengabdian Masyarakat, 2026)
This community service activity took place in Nanjungjaya village, Kersamanah district, Garut Regency with the goal to improve reading interest to MI As-Sibyan students through the establishment of a library in MI As-Sibyan. This activity is carried out by student group KKN 91 UIN Sunan Gunung Djati Bandung as part of the Community Service (KKN) program and used qualitative method through interview, observation and documentation and the implementation phase is divided into three, there are the first phase (early planning), second phase (library preparation), and third phase (library implementation). First phase covers the planning of book donation, socialization, and library decoration. Phase two covers the execution of socialization and library room preparation. Phase three covers the inauguration of the library opening. The result from this activity is with the establishment of the library it will be the strategic step to broaden knowledge access, develop reading interest, and strengthen the learning quality in both the school and local communities. The conclusion from this activity is giving education and facility to improve MI As-Sibyan students’ reading literacy. Keywords: Library, reading interest, community service